2x-y 3z=-1;-4x 2y-6z=2 by gauss elimination and back substitution

Printable View

- Sep 14th 2010, 09:30 PMsoniElimination Method
2x-y 3z=-1;-4x 2y-6z=2 by gauss elimination and back substitution

- Sep 14th 2010, 09:50 PMUnknown008
Could you re-post your equations? There are two equations with three unknowns and the '+' signs didn't appear, if there were any.

- Sep 14th 2010, 09:53 PMEducated
1. $\displaystyle 2x-y 3z=-1$

2. $\displaystyle -4x + 2y-6z=2$

I'm guessing it's a +2y and +3z

Here, double equation 1, $\displaystyle 2x-y 3z=-1$ to get $\displaystyle 4x-2y + 6z=-2$

Or conversely you could halve equation 2.

Then you have:

1. $\displaystyle 4x -2y + 6z=-2$

2. $\displaystyle -4x + 2y -6z=2$

Wait... here I find that both equations are the exact same... You can't solve a simultaneous eauation if both of them are the same.